Media Game Edukasi Berbasis Konservasi pada Tema Lingkungan di TK PKK Sikur Barat 01 - Lia Rismawati (Literasi: Jurnal Pendidikan Guru Indonesia, 2022)
This study aims to produce valid and effective learning media. This type of research is research and development (R & D) using the Borg and Gall model modified by Sukmadinata covering three stages, namely: (1) preliminary study; (2) preparation of product drafts; and (3) development. The learning media developed is the "Snakes and Ladders" Educational Gambe Media. The subjects in this study were 25 children in group B TK PKK Sikur Barat 01. Class B1 as the control class and B2 as the experimental class. Data was taken using expert validation sheets and character development observation sheets. Data were analyzed by descriptive, normality test, homogeneity test and effectiveness test by t-test. The results of the validator's assessment of the conservation-based learning model is an average of 3.25 including the good category. Field trials were declared effective with an average score of the development of children's environmental conservation values in the experimental class (38.8) better than the control class (22.0). Therefore it can be concluded that the educational game learning media "snakes and ladders" is valid and effective for developing students' awareness of environmental conservation.